Human umbilical cord mesenchymal stem cells decellular matrix alleviates chondrocyte senescence by inhibiting the STING-NF-κB pathway - Yuelong Zhang; Xunshan Ren; Huangming Zhuang; Huajie Li; Miradj Siddick Adam; Rongling Feng; Junming Zhu; Panghu Zhou (PLoS ONE, 2025)
Osteoarthritis (OA), characterized by synovial inflammation, articular cartilage degeneration, and structural changes of subchondral bone and periarticular tissues, represents a major unmet clinical challenge. Targeting senescent chondrocytes has emerged as a promising therapeutic strategy of OA. Human umbilgratical cord mesenchymal stem cells (hUCMSCs) have shown potential in OA treatment through paracrine mechanisms, but their clinical translation is limited by challenges in cell viability control and safety concerns. hUCMSCs decellular extracellular matrix (hUCMSCs-dECM) can target senescent chondrocytes to alleviate senescence in OA. Stimulator of interferon gene (STING) can promote chondrocyte senescence in OA through the activation of NF-κB signaling, and inhibition of STING may provide a novel approach for OA treatment. Here, we demonstrated that hUCMSCs-dECM attenuated chondrocyte senescence in vivo and in vitro by inhibiting the STING-NF-κB pathway, which would provide a novel approach for OA treatment.